Lakon Wahyu Cakraningrat dalam Paradigma Strukturalisme - ARIS WAHYUDI (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2008)
Wahyu Cakraningrat Play in Structuralism Paradigm. Lakon Wahyu Cakraningrat as a cultural phenomenonis basically a means of communication between composer with readers, viewers and listeners to the puppeteer.It is created by using a symbol system in the puppet, so that in every play of puppet, it always contains the meaningwhich can be known and understood well by the composer, puppeteer, and the community. These rules manage thesystem of symbols in the phenomenon of puppet plays, in their capacity as the “grammar” puppet plays with usingLevi-Strauss’s structuralism paradigm. This is going to be gained the interpretation that Lakon Wahyu Cakraningratis a work of art presenting some knowledge of Javanese culture.